"It is always HIV/AIDS and TB": Home-based carers' perspectives on epilepsy in Cape Town, South Africa. Issue 1 (1st January 2016) - Keikelame, Mpoe Johannah; Swartz, Leslie
Abstract : The study highlights the complex cultural religious factors affecting epilepsy and a need for integrated home-based care services. Two focus group discussions exploring home-based carers' (HBCs) perspectives on epilepsy were conducted using a semi-structured focus group interview guide, which was based on Kleinman's explanatory model framework. The audio-recorded data were transcribed verbatim, and a thematic analysis was done. The three main themes were epilepsy names and metaphors, religious beliefs about the cause and treatment of epilepsy, and HBCs' perceived roles and strategies for engaging in epilepsy care. Findings provide some insights for research, policy, and practice.